2020
DOI: 10.4274/tjo.galenos.2020.29939
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Ganglion Cell Layer Thickness in the Early Period After Femtosecond LASIK Surgery

Abstract: Objectives: To evaluate the early effects of femtosecond laser-assisted in situ keratomileusis (LASIK) surgery in a healthy population on the retinal ganglion cell thickness (GCT), peripapillary retinal nerve fiber thickness (NFT), and central macular thickness (CMT) obtained by spectral domain optical coherence tomography (SD-OCT). Materials and Methods: This case-control study included data from the right eye of 40 subjects without any disease other than refractive error and who had undergone femtosecond las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In conclusion, there was no change in GCT, NFT, and CMT measured by the SD-OCT in the early period after femtosecond LASIK surgery and this goes in accordance with our study. [5] Another study conducted by El-Mahdy et al (2020) to assess structural and functional changes of macular and NFL using spectral domain optical coherence tomography (SD-OCT) following LASIK surgery using Moria microkeratome. They found that there was no statistically significant correlation between the effect of suction by microkeratome during LASIK surgery and its efficacy on macular and retinal nerve fiber layer.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, there was no change in GCT, NFT, and CMT measured by the SD-OCT in the early period after femtosecond LASIK surgery and this goes in accordance with our study. [5] Another study conducted by El-Mahdy et al (2020) to assess structural and functional changes of macular and NFL using spectral domain optical coherence tomography (SD-OCT) following LASIK surgery using Moria microkeratome. They found that there was no statistically significant correlation between the effect of suction by microkeratome during LASIK surgery and its efficacy on macular and retinal nerve fiber layer.…”
Section: Discussionmentioning
confidence: 99%